The Exact Solutions for Several Partial Differential-Difference Equations with Constant Coefficients - Hongyan Xu; Ling Xu; Hari Mohan Srivastava (Mathematics, 2022)
This article is concerned with the description of the entire solutions of several Fermat type partial differential-difference equations (PDDEs) <semantics><mfenced separators="" open="[" close="]">μf(z)+λfz1(z)</mfenced>2+[αf(z+c)−βf(z)]2=1,</semantics> and <semantics><mfenced separators="" open="[" close="]">μf(z)+λ1fz1(z)+λ2fz2(z)</mfenced>2+[αf(z+c)−βf(z)]2=1,</semantics> where <semantics>fz1(z)=∂f∂z1</semantics> and <semantics>fz2(z)=∂f∂z2</semantics>, <semantics>c=(c1,c2)∈C2</semantics>, <semantics>α,β,μ,λ,λ1,λ2,c1,c2</semantics> are constants in <semantics>C</semantics>. Our theorems in this paper give some descriptions of the forms of transcendental entire solutions for the above equations, which are some extensions and improvement of the previous theorems given by Xu, Cao, Liu, and Yang. In particular, we exhibit a series of examples to explain that the existence conditions and the forms of transcendental entire solutions with a finite order of such equations are precise.